Do International Roaming Alliances Harm Consumers?1. (December 2015) - Buehler, Benno
Abstract : This paper develops a model of international roaming in which mobile network operators (MNO's) compete both on the wholesale market to sell roaming services to foreign operators and on the retail market for subscribers. To allow their subscribers to place or receive calls abroad, they have to buy roaming services provided by foreign MNO's. In the absence of international alliances, competition between foreign operators would drive wholesale unit prices down to marginal costs. However, international alliances are endogenously formed since they serve as a commitment device to soften competition on the retail market, leading to excessively high roaming per‐call prices.